The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11115-020-00472-7
|View full text |Cite
|
Sign up to set email alerts
|

Public Versus Private Job Satisfaction. Is there a Trade-off between Wages and Stability?

Abstract: consensus, however, on whether these differences lead to greater job satisfaction and if, on average, the public sector employee job satisfaction is higher than that of those in the private sector.The results in the different studies are also conditioned by the cultural, economic and socio-political context of the reference country, so it is expected that the comparison of job satisfaction levels between public and private workers will differ in different regional contexts. Specifically, the Spanish labour mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Our variable under study-working in the public sectorhas a positive and significant influence on job satisfaction, in line with our initial hypothesis and the works of Steel and Warner (1990), Maidani (1991), DeSantis and Durst (1996), Demoussis and Giannakopoulos (2007), and Sánchez-Sánchez and Fernández (2020). The coefficient is positive even when variables associated with job instability are included, which implies that there are other factors that justify greater satisfaction in the public sector.…”
Section: Resultssupporting
confidence: 82%
“…Our variable under study-working in the public sectorhas a positive and significant influence on job satisfaction, in line with our initial hypothesis and the works of Steel and Warner (1990), Maidani (1991), DeSantis and Durst (1996), Demoussis and Giannakopoulos (2007), and Sánchez-Sánchez and Fernández (2020). The coefficient is positive even when variables associated with job instability are included, which implies that there are other factors that justify greater satisfaction in the public sector.…”
Section: Resultssupporting
confidence: 82%
“…The first outcome of the present study revealed that public employees are more satisfied with their work than their private counterparts. This is the first evidence of this sort obtained from Spain and aligns with previous studies that also confirm greater satisfaction among public employees (Demoussis and Giannakopoulos, 2007;Mihajlov and Mihajlov, 2016b;S anchez-S anchez and Fern andez Puente, 2020;Steel and Warner, 1990;Steijn, 2008; Notes: þ p < 0.1; *p < 0.05; **p < 0.01; ***p < 0.001 Zeffane and Bani Melhem, 2017). Although generalizability is not recommended as these countries may have different working conditions, Demoussis and Giannakopoulos (2007) used a sample of Greek employees and Zeffane and Bani Melhem (2017) used a sample of public and private employees from the service sector in the United Arab Emirates and provided results that confirmed our findings.…”
Section: Mediating Role Of Job Demandssupporting
confidence: 91%
“…One of the Mediating role of job demands debates in the literature on employee satisfaction in the public sector has to do with the question of whether public employees are more or less satisfied than their private sector counterparts (Bright, 2008). Whereas some studies have found that public employees are more satisfied (Demoussis and Giannakopoulos, 2007;Mihajlov and Mihajlov, 2016b;S anchez-S anchez and Fern andez Puente, 2020;Steel and Warner, 1990;Steijn, 2008;Zeffane and Bani Melhem, 2017), others have found the opposite (Borges, 2013;Burke and Singh, 2016). Therefore, the debate is still open.…”
Section: Introductionmentioning
confidence: 99%
“…Or it might simply be that women pay more attention to different resources than men do. Somewhat surprisingly, the analysis did not uncover any striking differences in efficiency levels between private and public sectors, despite several previous studies explicitly distinguishing and comparing job satisfaction measures between private and public sector domains [46][47][48].…”
Section: Discussionmentioning
confidence: 59%